Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1399-6576.2009.01920.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between central venous pressure and blood loss during hepatic resection in 984 living donors

Abstract: CVP during hepatic resection was not associated with intraoperative blood loss in living liver donors, suggesting that CVP may not be an important factor in predicting blood loss during hepatectomy in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 17 publications
1
46
1
1
Order By: Relevance
“…Low CVP during liver resection is thought to reflect low hepatic sinusoid pressure, reducing parenchymal congestion. To date, however, maintaining low CVP during hepatectomy to reduce blood loss is controversial, especially in healthy living donors [1,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Low CVP during liver resection is thought to reflect low hepatic sinusoid pressure, reducing parenchymal congestion. To date, however, maintaining low CVP during hepatectomy to reduce blood loss is controversial, especially in healthy living donors [1,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…13 Compared with previous studies, intraoperative transfusions were more frequently used in our study. 5,11,14 The discrepancy between our study and others may arise from the different definitions of intraoperative transfusion that were used. Previous studies have reported the frequency of whole blood or packed red blood cell transfusions as the intraoperative transfusion.…”
Section: Discussionmentioning
confidence: 42%
“…Ryu and associates 26 and Melendez and associates 27 have reported that a low central venous pressure may help minimize blood loss without adversely affecting organ perfusion during donor hepatectomy. In contrast to these findings, in a large series of 984 living donors, Kim and associates 11 showed no association between central venous pressure and intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…[11] Whereas retrospective reviews of living related donor hepatectomies have reported that CVP monitoring did not reduce blood loss, and that blood loss did not correlate with CVP level. [12,13,14] Reduced blood loss can be attributed to the fact that hepatic venous pressure is dependent on central venous pressure. Low CVP increases negative pressure gradient with respect to right atrium and increase in air embolism which can be detected by transechocardiography.…”
Section: Discussion:-mentioning
confidence: 99%